2019
DOI: 10.1007/s11367-019-01650-6
|View full text |Cite
|
Sign up to set email alerts
|

Consequential LCA and LCC using linear programming: an illustrative example of biorefineries

Abstract: Purpose This paper aims to demonstrate how LCA can be improved by the use of linear programming (LP) (i) to determine the optimal choice between new technologies, (ii) to identify the optimal region for supplying the feedstock, and (iii) to deal with multifunctional processes without specifying a certain main product. Furthermore, the contribution of LP in the context of consequential LCA and LCC is illustrated. Methods We create a mixed integer linear program (MILP) for the environmental and economic assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Such an integrated and multi-level approach can help obtain a clearer understanding of the potential impacts caused by the increased use of biomass resources and at what scale these impacts might be occurring. Environmental, social, and economic impacts not only occur directly within the producing region, but can also be induced elsewhere, outside of these bioeconomy regions, due to the production activities of the various bioeconomy clusters and networks [26,[30][31][32][33]. This leads to a quandary of scale when making impact assessments of bio-based systems, i.e., at which scale should assessments be carried out [34].…”
Section: Biomass Resourcesmentioning
confidence: 99%
“…Such an integrated and multi-level approach can help obtain a clearer understanding of the potential impacts caused by the increased use of biomass resources and at what scale these impacts might be occurring. Environmental, social, and economic impacts not only occur directly within the producing region, but can also be induced elsewhere, outside of these bioeconomy regions, due to the production activities of the various bioeconomy clusters and networks [26,[30][31][32][33]. This leads to a quandary of scale when making impact assessments of bio-based systems, i.e., at which scale should assessments be carried out [34].…”
Section: Biomass Resourcesmentioning
confidence: 99%
“…Thus, ECOPT 2 aims to model the direct and indirect environmental impacts associated with an internally consistent technology transition scenario. While previous studies have combined some of these elements, such as combining LP and LCA, the focus of their work was to determine the environmentally optimal substitution mix for static systems (Budzinski et al., 2019; Saner et al., 2014; Steubing et al., 2016). In contrast, LP is used in ECOPT 2 toward understanding the dynamics of technology deployment while taking into consideration stock and material cycle dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of joint LCA and optimization approaches are two‐fold: it allows the inclusion of supply constraints, and by default, the optimization approach finds the combination of decision variables that result in the lowest environmental impacts. Examples of joint LCA‐optimization studies generally involve the selection of technologies by minimizing environmental impact, and using as decision variables, for example, the mix of substitutable products with limited supply as in Budzinski et al (2019), Saner et al (2014), and Steubing et al (2016), among others. These studies, however, have been static in nature and do not identify a transition pathway.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, MCDA, TEA, and life cycle costing (LCC) are just a few examples of methods that can be found in some recent applications, although these are not yet widely used. This also includes the application of linear programming methods in consequential approaches, as can be found in [52]. A recent stream of LCA called the life cycle sustainability Assessment (LCSA) tends to embrace such a multi method approach [53,54].…”
Section: Ex-ante Lca and Multi Methods Approachesmentioning
confidence: 99%
“…In other LCA studies where the aim is not necessarily to perform an ex there are ample opportunities to apply other methods to support or extend t For instance, MCDA, TEA, and life cycle costing (LCC) are just a few e methods that can be found in some recent applications, although these are no used. This also includes the application of linear programming methods in co approaches, as can be found in [52]. A recent stream of LCA called the lif tainability Assessment (LCSA) tends to embrace such a multi method appro Several years ago, [55] performed a review on LCSA applications and found ods to deepen LCSA were lacking, proposing systems thinking and related tentially valuable to deepen the analyses.…”
Section: An Overview Of Recent Plastics and Recycling Lca Studiesmentioning
confidence: 99%